RGS5 promotes arterial growth during arteriogenesis. Issue 8 (27th June 2014) - Arnold, Caroline; Feldner, Anja; Pfisterer, Larissa; Hödebeck, Maren; Troidl, Kerstin; Genové, Guillem; Wieland, Thomas; Hecker, Markus; Korff, Thomas
Abstract Arteriogenesis—the growth of collateral arterioles—partially compensates for the progressive occlusion of large conductance arteries as it may occur as a consequence of coronary, cerebral or peripheral artery disease. Despite being clinically highly relevant, mechanisms driving this process remain elusive. In this context, our study revealed that abundance of regulator of G‐protein signalling 5 (RGS5) is increased in vascular smooth muscle cells (SMCs) of remodelling collateral arterioles. RGS5 terminates G‐protein‐coupled signalling cascades which control contractile responses of SMCs. Consequently, overexpression of RGS5 blunted Gαq/11‐mediated mobilization of intracellular calcium, thereby facilitating Gα12/13‐mediated RhoA signalling which is crucial for arteriogenesis. Knockdown of RGS5 evoked opposite effects and thus strongly impaired collateral growth as evidenced by a blockade of RhoA activation, SMC proliferation and the inability of these cells to acquire an activated phenotype in RGS5‐deficient mice after the onset of arteriogenesis. Collectively, these findings establish RGS5 as a novel determinant of arteriogenesis which shifts G‐protein signalling from Gαq/11‐mediated calcium‐dependent contraction towards Gα12/13‐mediated Rho kinase‐dependent SMC activation.